Clearing the Air: Asthma and Indoor Air Exposures - Institute of Medicine (The National Academies Press, 2000)
Since about 1980, asthma prevalence and asthma-related hospitalizations and deaths have increased substantially, especially among children. Of particular concern is the high mortality rate among African Americans with asthma. Recent studies have suggested that indoor exposures2014to dust mites, cockroaches, mold, pet dander, tobacco smoke, and other biological and chemical pollutants2014may influence the disease course of asthma. To ensure an appropriate response, public health and education officials have sought a science-based assessment of asthma and its relationship to indoor air exposures. Clearing the Air meets this need. This book examines how indoor pollutants contribute to asthma2014its causation, prevalence, triggering, and severity. The committee discusses asthma among the general population and in sensitive subpopulations including children, low-income individuals, and urban residents. Based on the most current findings, the book also evaluates the scientific basis for mitigating the effects of indoor air pollutants implicated in asthma. The committee identifies priorities for public health policy, public education outreach, preventive intervention, and further research.

Review of ONR's Uninhabited Combat Air Vehicles Program - National Research Council (The National Academies Press, 2000)
Joint Vision 20101 addresses the need for achieving military dominance through the application of new operational concepts. For the Department of the Navy, future operational concepts will hinge on a continuance of forward yet unobtrusive presence and the capability to influence events ashore as required. This capability will be enabled by the development and insertion into the forces of new technologies for providing command, control, and surveillance; battlespace dominance; power projection; and force sustainment. For example, unmanned aerial vehicles (UAVs) have recently proven to be valuable operational platforms for providing tactical intelligence by surveillance of the battlefield. To support naval force objectives, the Office of Naval Research (ONR) has established a research program within the Strike Technology Division (Code 351) of the Naval Expeditionary Warfare Science and Technology Department aimed at expanding the operational capabilities of UAVs to include not only surveillance and reconnaissance, but strike and logistics missions as well. This new class of autonomous vehicles, known as uninhabited combat air vehicles (UCAVs), is foreseen as being intelligent, recoverable, and highly maneuverable in support of future naval operations. Review of ONR'S Uninhabited Combat Air Vehicles Program evaluates ONR's UCAV technology activities, including its vision documents and its science and technology roadmap (in areas of vehicle dynamics, communications, sensors, and autonomous agents) against criteria that would be selected by the committee, such as the relevance for meeting future naval priorities, the cost and time scale for its utilization, duplication of effort, and scientific and technical quality.

Watershed Management for Potable Water Supply: Assessing the New York City Strategy - National Research Council (The National Academies Press, 2000)
In 1997, New York City adopted a mammoth watershed agreement to protect its drinking water and avoid filtration of its large upstate surface water supply. Shortly thereafter, the NRC began an analysis of the agreement's scientific validity. The resulting book finds New York City's watershed agreement to be a good template for proactive watershed management that, if properly implemented, will maintain high water quality. However, it cautions that the agreement is not a guarantee of permanent filtration avoidance because of changing regulations, uncertainties regarding pollution sources, advances in treatment technologies, and natural variations in watershed conditions. The book recommends that New York City place its highest priority on pathogenic microorganisms in the watershed and direct its resources toward improving methods for detecting pathogens, understanding pathogen transport and fate, and demonstrating that best management practices will remove pathogens. Other recommendations, which are broadly applicable to surface water supplies across the country, target buffer zones, stormwater management, water quality monitoring, and effluent trading.

Ending Neglect: The Elimination of Tuberculosis in the United States - Institute of Medicine (The National Academies Press, 2000)
Tuberculosis emerged as an epidemic in the 1600s, began to decline as sanitation improved in the 19th century, and retreated further when effective therapy was developed in the 1950s. TB was virtually forgotten until a recent resurgence in the U.S. and around the world2014ominously, in forms resistant to commonly used medicines. What must the nation do to eliminate TB? The distinguished committee from the Institute of Medicine offers recommendations in the key areas of epidemiology and prevention, diagnosis and treatment, funding and organization of public initiatives, and the U.S. role worldwide. The panel also focuses on how to mobilize policy makers and the public to effective action. The book provides important background on the pathology of tuberculosis, its history and status in the U.S., and the public and private response. The committee explains how the U.S. can act with both self-interest and humanitarianism in addressing the worldwide incidence of TB.

Research Needs in Subsurface Science - National Research Council (The National Academies Press, 2000)
Research Needs in Subsurface Science provides an overview of the subsurface contamination problems across the DOE complex and shows by examples from the six largest DOE sites (Hanford Site, Idaho Engineering and Environmental Laboratory, Nevada Test Site, Oak Ridge Reservation, Rocky Flats Environmental Technology Site, and Savannah River Site) how advances in scientific and engineering knowledge can improve the effectiveness of the cleanup effort. This report analyzes the current Environmental Management (EM) Science Program portfolio of subsurface research projects to assess the extent to which the program is focused on DOE's contamination problems. This analysis employs an organizing scheme that provides a direct linkage between basic research in the EM Science Program and applied technology development in DOE's Subsurface Contaminants Focus Area. Research Needs in Subsurface Science also reviews related research programs in other DOE offices and other federal agencies (see Chapter 4) to determine the extent to which they are focused on DOE's subsurface contamination problems. On the basis of these analyses, this report singles out the highly significant subsurface contamination knowledge gaps and research needs that the EM Science Program must address if the DOE cleanup program is to succeed.

Advanced Epitaxy for Future Electronics, Optics, and Quantum Physics - Arthur C. Gossard (The National Academies Press, 2000)
The future development of electronics, optics, and, quite probably, quantum physics is being driven by advances in epitaxial materials. Band gap engineering, wafer bonding techniques, and epitaxial regrowth technology will push transistors far beyond the present speed barriers. Oxide growth within epitaxial layer structures and new advances in tunnel structures will push the development of the next generation of high-performance laser arrays and of efficient cascade laser designs. Perfection of the growth of semiconductor nitrides will move future electronics to higher powers and to suitability for extreme environments while revolutionizing lighting and display. Growth technologies to incorporate metallic particles and magnetic elements within high-quality semiconductors promise ultrafast electro-optical components for chemical and biological applications as well as electronically controlled magnetism for future memories and electrical\/magnetic hybrid devices. Quantum dot materials will lead the field of signal electronics while hopefully providing a new proving and discovery ground for quantum physics. This paper dicusses the current progress in these areas.

Methyl Bromide Risk Characterization in California - National Research Council (The National Academies Press, 2000)
Methyl bromide is gaseous pesticide used to fumigate soil, crops, commodity warehouses, and commodity-shipping facilities. Up to 17 million pounds of methyl bromide are used annually in California to treat grapes, almonds, strawberries, and other crops. Methyl bromide is also a known stratospheric ozone depleter and, as such, is scheduled to be phased out of use in the United States by 2005 under the United Nations Montreal Protocol. In California, the use of methyl bromide is regulated by the Department of Pesticide Regulation (DPR), which is responsible for establishing the permit conditions that govern the application of methyl bromide for pest control. The actual permits for use are issued on a site-specific basis by the local county agricultural commissioners. Because of concern for potential adverse health effects, in 1999 DPR developed a draft risk characterization document for inhalation exposure to methyl bromide. The DPR document is intended to support new regulations regarding the agricultural use of this pesticide. The proposed regulations encompass changes to protect children in nearby schools, establish minimum buffer zones around application sites, require notification of nearby residents, and set new limits on hours that fumigation employees may work. The State of California requires that DPR arrange for an external peer review of the scientific basis for all regulations. To this end, the National Research Council (NRC) was asked to review independently the draft risk characterization document prepared by DPR for inhalation exposure to methyl bromide. The task given to NRC's subcommittee on methyl bromide states the following: The subcommittee will perform an independent scientific review of the California Environmental Protection Agency's risk assessment document on methyl bromide. The subcommittee will (1) determine whether all relevant data were considered, (2) determine the appropriateness of the critical studies, (3) consider the mode of action of methyl bromide and its implications in risk assessment, and (4) determine the appropriateness of the exposure assessment and mathematical models used. The subcommittee will also identify data gaps and make recommendations for further research relevant to setting exposure limits for methyl bromide. This report evaluates the toxicological and exposure data on methyl bromide that characterize risks at current exposure levels for field workers and nearby residents. The remainder of this report contains the subcommittee's analysis of DPR's risk characterization for methyl bromide. In Chapter 2, the critical toxicological studies and endpoints identified in the DPR document are evaluated. Chapter 3 summarizes DPR's exposure assessment, and the data quality and modeling techniques employed in its assessment are critiqued. Chapter 4 provides a review of DPR's risk assessment, including the adequacy of the toxicological database DPR used for hazard identification, an analysis of the margin-of-exposure data, and appropriateness of uncertainty factors used by DPR. Chapter 5 contains the subcommittee's conclusions about DPR's risk characterization, highlights data gaps, and makes recommendations for future research.

Making IT Better: Expanding Information Technology Research to Meet Society's Needs - National Research Council (The National Academies Press, 2000)
The flood of information technology (I.T.) products and services entering the market place often obscures the need to nurture the research enterprise. But as I.T. becomes integrated into all aspects of society, the need for research is even greater. And the range of issues that need to be addressed is broader than ever. This new book highlights the fundamental importance of research to ensure that I.T. meets society's expanding needs. Against the background of dramatic change in the I.T. landscape, the committee examines four key questions: Is the scope of I.T. research broad enough2014particularly in the arena of large-scale systems2014to address government, business, and social applications? Are government and industrial sponsors providing sufficient funding for I.T. research? Is the research net big both big and diverse enough to capture sufficient financial and intellectual resources to advance the field? Are structures and mechanisms for funding and conducting research suited to the new sets of research challenges?

Review of the U.S. Navy's Exposure Standard for Manufactured Vitreous Fibers - National Research Council (The National Academies Press, 2000)
Manufactured vitreous fibers (MVF), also known as synthetic vitreous fibers, are considered to be less hazardous than asbestos to human health. They are used in many thermal- and acoustical-insulation applications as an asbestos substitute or as a filtration medium. The Navy uses MVF in shipboard and onshore applications. To protect Navy personnel from harmful exposures to MVF, the U.S. Navy Environmental Health Center (NEHC) developed occupational exposure standards. The documentation assists industrial hygienists, occupational medicine physicians, and other Navy health professionals in assessing and controlling the health hazards linked with exposure to MVF. In 1997, the National Research Council (NRC) was asked to conduct an independent review of the Navy's toxicological assessment of MVF and to evaluate the scientific validity of its exposure standard of 2 fibers per cubic centimeter of air (f\/cm3). The NRC assigned the task to the Committee on Toxicology, which established the Subcommittee on Manufactured Vitreous Fibers, a multidisciplinary group of experts, to determine whether all relevant toxicological and epidemiological data were correctly considered in developing the exposure standard; and to examine the uncertainty, variability, and quality of data and the appropriateness of assumptions used in the derivation of the exposure standard. The subcommittee was also asked to identify deficiencies in the MVF database and, where appropriate, to make recommendations for future research and data development. Review of the U.S. Navy's exposure Standard for Manufactured Vitreous Fibers represents the subcommittee's final report. The committee had expanded its review when in January 1999, the Navy revised its Occupational Safety and Health Program Manual (CNO 1999), changing the occupational exposure limit for MVF to the American Conference of Governmental Industrial Hygienists (ACGIH) threshold limit value (TLV) of 1 f\/cm3. The report features recommendations by the subcommittee as well as information gaps found throughout investigation. Overall, the subcommittee found that the Navy made a good start in assessing the health effects of MVF, but needed further research.

Dietary Reference Intakes for Vitamin C, Vitamin E, Selenium, and Carotenoids - Institute of Medicine
This volume is the newest release in the authoritative series of quantitative estimates of nutrient intakes to be used for planning and assessing diets for healthy people. Dietary Reference Intakes (DRIs) is the newest framework for an expanded approach developed by U.S. and Canadian scientists. This book discusses in detail the role of vitamin C, vitamin E, selenium, and the carotenoids in human physiology and health. For each nutrient the committee presents what is known about how it functions in the human body, which factors may affect how it works, and how the nutrient may be related to chronic disease. Dietary Reference Intakes provides reference intakes, such as Recommended Dietary Allowances (RDAs), for use in planning nutritionally adequate diets for different groups based on age and gender, along with a new reference intake, the Tolerable Upper Intake Level (UL), designed to assist an individual in knowing how much is \

Enhancing Data Systems to Improve the Quality of Cancer Care - Institute of Medicine; National Research Council (The National Academies Press, 2000)
One of the barriers to improving the quality of cancer care in the United States is the inadequacy of data systems. Out-of-date or incomplete information about the performance of doctors, hospitals, health plans, and public agencies makes it hard to gauge the quality of care. Augmenting today's data systems could start to fill the gap. This report examines the strengths and weaknesses of current systems and makes recommendations for enhancing data systems to improve the quality of cancer care. The board's recommendations fall into three key areas: Enhance key elements of the data system infrastructure (i.e., quality-of-care measures, cancer registries and databases, data collection technologies, and analytic capacity). Expand support for analyses of quality of cancer care using existing data systems. Monitor the effectiveness of data systems to promote quality improvement within health systems.

Education and Delinquency: Summary of a Workshop - National Research Council; Institute of Medicine (The National Academies Press, 2000)
The Panel on Juvenile Crime: Prevention, Treatment, and Control convened a workshop on October 2, 1998, to explore issues related to educational performance, school climate, school practices, learning, student motivation and commitment to school, and their relationship to delinquency. The workshop was designed to bring together researchers and practitioners with a broad range of perspectives on the relationship between such specific issues as school safety and academic achievement and the development of delinquent behavior. Education and Delinquency reviews recent research findings, identifies gaps in knowledge and promising areas of future research, and discusses the need for program evaluation and the integration of empirical research findings into program design.

Toxicological Risks of Selected Flame-Retardant Chemicals - National Research Council (The National Academies Press, 2000)
Ignition of upholstered furniture by small open flames from matches, cigarette lighters, and candles is one of the leading causes of residential-fire deaths in the United States. These fires accounted for about 16% of civilian fire deaths in 1996. On average, each year since 1990, about 90 deaths (primarily of children), 440 injuries, and property losses amounting to 50 million dollars have resulted from fires caused by the ignition of upholstered furniture by small open flames. Certain commercial seating products (such as aircraft and bus seats) are subject to flammability standards and sometimes incorporate FR-treated upholstery cover materials, but there is no federal-government requirement for residential upholstered furniture, and it is generally not treated with FR chemicals. It is estimated that less than 0.2% of all U.S. residential upholstery fabric is treated with flame-retardant (FR) chemicals. The Consumer Product Safety Act of 1972 created the U.S. Consumer Product Safety Commission (CPSC) as an independent federal regulatory agency whose mission is to protect the public from unreasonable risks of injury and death associated with consumer products. CPSC also administers the Flammable Fabrics Act, under which it regulates flammability hazards and the Federal Hazardous Substances Act (FHSA), which regulates hazardous substances including chemicals. In 1993, the National Association of State Fire Marshals petitioned CPSC to issue a performance-based flammability standard for upholstered furniture to reduce the risk of residential fires. The Commission granted that portion of the petition relating to small open flame ignition risks. In response to concerns regarding the safety of FR chemicals, Congress, in the fiscal year 1999 appropriations report for CPSC, requested that the National Research Council conduct an independent study of the health risks to consumers posed by exposure to FR chemicals that are likely to be used in residential upholstered furniture to meet a CPSC standard. The National Research Council assigned the project to the Committee on Toxicology (COT) of the Commission on Life Sciences' Board on Environmental Studies and Toxicology. COT convened the Subcommittee on Flame-Retardant Chemicals, which prepared this report. Subcommittee members were chosen for their recognized expertise in toxicology, pharmacology, epidemiology, chemistry, exposure assessment, risk assessment, and biostatistics. Toxicological Risks of Selected Flame-Retardant Chemicals is organized into 18 chapters and two appendices. Chapter 2 describes the risk assessment process used by the subcommittee in determining the risk associated with potential exposure to the various FR chemicals. Chapter 3 describes the method the subcommittee used to measure and estimate the intensity, frequency, extent, and duration of human exposure to FR chemicals. Chapters 4-19 provide the subcommittee's review and assessment of health risks posed by exposure to each of the 16 FR chemicals. Data gaps and research needs are provided at the end of these chapters.

Seeing into the Earth: Noninvasive Characterization of the Shallow Subsurface for Environmental and Engineering Applications - National Research Council (The National Academies Press, 2000)
Just below our feet is an environment that supports our infrastructure, yields water, provides for agriculture, and receives our waste. Our capacity to describe, or characterize, this environment is crucial to the solution of many resource, environmental, and engineering problems. And just as medical imaging technologies have reduced the need for exploratory surgeries, a variety of technologies hold the promise for rapid, relatively inexpensive noninvasive characterization of the Earth's subsurface. Seeing into the Earth examines why noninvasive characterization is important and how improved methods can be developed and disseminated. Looking at the issues from both the commercial and public perspectives, the volume makes recommendations for linking characterization and cost savings, closing the gap between the state of science and the state of the practice, and helping practitioners make the best use of the best methods. The book provides background on: The role of noninvasive subsurface characterization in contaminant cleanup, resource management, civil engineering, and other areas. The physical, chemical, biological, and geological properties that are characterized. Methods of characterization and prospects for technological improvement. Certain to be important for earth scientists and engineers alike, this book is also accessible to interested lay readers.

Buzzwords: A Scientist Muses on Sex, Bugs, and Rock 'n' Roll - May R. Berenbaum
What sort of person devotes their life to the study of bugs? How do you picture your average, every-day entomologist? \

Marine Mammals and Low-Frequency Sound: Progress Since 1994 - National Research Council (The National Academies Press, 2000)
Sound has become a major tool for studying the ocean. Although the ocean is relatively opaque to light, it is relatively transparent to sound. Sound having frequencies below 1,000 Hertz (Hz) is often defined as low-frequency sound. The speed of sound is proportional to the temperature of the water through which it passes. Therefore, sound speed can be used to infer the average temperature of the water volume through which sound waves have passed. The relationship between water temperature and the speed of sound is the basis for the Acoustic Thermometry of Ocean Climate (ATOC) experiment. The ATOC experiment is designed to monitor the travel time of sound between sources off the coasts of Hawaii and California and several receivers around the Pacific Ocean in order to detect trends in ocean temperature and for other research and monitoring purposes. Some whales, seals, and fish use low-frequency sound to communicate and to sense their environments. For example, baleen whales and some toothed whales are known to use and respond to low-frequency sound emitted by other individuals of their species. Sharks are not known to produce low-frequency sound but are attracted to pulsed low-frequency sounds. Therefore, it is possible that human-generated low-frequency sound could interfere with the natural behavior of whales, sharks, and some other marine animals. Marine Mammals and Low-Frequency Sound is an updated review of the National Research Council 1994 report Low-Frequency Sound and Marine Mammals: Current Knowledge and Research Needs, based on data obtained from the MMRP and results of any other relevant research, including ONR's research program in low-frequency sound and marine mammals. This report compares new data with the research needs specified in the 1994 NRC report, focusing on the strengths and weaknesses of the data for answering important outstanding questions about marine mammal responses to low-frequency sound and identifies areas where gaps in our knowledge continue to exist.

One Universe: At Home in the Cosmos - Neil de Grasse Tyson; Charles Liu; Robert Irion (The National Academies Press, 2000)
A new window opens onto the cosmos... Almost every day we are challenged by new information from the outermost reaches of space. Using straightforward language, One Universe explores the physical principles that govern the workings of our own world so that we can appreciate how they operate in the cosmos around us. Bands of color in a sunlit crystal and the spectrum of starlight in giant telescopes, the arc of a hard-hit baseball and the orbit of the moon, traffic patterns on a freeway and the spiral arms in a galaxy full of stars2014they're all tied together in grand and simple ways. We can understand the vast cosmos in which we live by exploring three basic concepts: motion, matter, and energy. With these as a starting point, One Universe shows how the physical principles that operate in our kitchens and backyards are actually down-to-Earth versions of cosmic processes. The book then takes us to the limits of our knowledge, asking the ultimate questions about the origins and existence of life as we know it and where the universe came from2014and where it is going. Glorious photographs2014many seen for the first time in these pages2014and original illustrations expand and enrich our understanding. Evocative and clearly written, One Universe explains complex ideas in ways that every reader can grasp and enjoy. This book captures the grandeur of the heavens while making us feel at home in the cosmos. Above all, it helps us realize that galaxies, stars, planets, and we ourselves all belong to One Universe.

Gulf War and Health: Volume 1: Depleted Uranium, Sarin, Pyridostigmine Bromide, and Vaccines - Institute of Medicine (The National Academies Press, 2000)
The men and women who served in the Gulf War theater were potentially exposed to a wide range of biological and chemical agents. Gulf War and Health: Volume 1 assesses the scientific literature concerning the association between these agents and the adverse health effects currently experienced by a large number of veterans.

Modeling Mobile-Source Emissions - Transportation Research Board; National Research Council (The National Academies Press, 2000)
The Mobile Source Emissions Factor (MOBILE) model is a computer model developed by the U.S. Environmental Protection Agency (EPA) for estimating emissions from on-road motor vehicles. MOBILE is used in air-quality planning and regulation for estimating emissions of carbon monoxide (CO), volatile organic compounds (VOCs), and nitrogen oxides (NOx) and for predicting the effects of emissions-reduction programs. Because of its important role in air-quality management, the accuracy of MOBILE is critical. Possible consequences of inaccurately characterizing motor-vehicle emissions include the implementation of insufficient controls that endanger the environment and public health or the implementation of ineffective policies that impose excessive control costs. Billions of dollars per year in transportation funding are linked to air-quality attainment plans, which rely on estimates of mobile-source emissions. Transportation infrastructure decisions are also affected by emissions estimates from MOBILE. In response to a request from Congress, the National Research Council established the Committee to Review EPA's Mobile Source Emissions Factor (MOBILE) Model in October 1998. The committee was charged to evaluate MOBILE and to develop recommendations for improving the model.

Cooperation in the Energy Futures of China and the United States–Chinese Version (The National Academies Press, 2000)